PENGEMBANGAN APLIKASI CUTI KARYAWAN DENGAN METODE AGILE BERBASIS WEB PADA PT BPR DANA MAKMUR BATAM - kendy; Fajrin, Alfannisa (LPPM Universitas Putera Batam, 2024)
Paid leave is temporary absence commonly used in companies. The purpose of using paid leave is not to come to work for a predetermined period of time which does not cut salary. Naturally, this is quite significant, particularly in the workplace, as if a business has staff who are not disciplined like they want to not come to work anytime, then admin can cut their salaries. There are various methods for applying for paid leave, starting from recording data manually, and through the system. In general, companies apply for paid leave using manualy system or paper methods. This can increase operating costs and result in excessive paper usage. PT. BPR Dana Makmur initially used manual or paper methods as a means to apply for paid leave. The researchers attempted to create a web-based application based on this issue. with the Agile leave application procedure and made it a research project. It is anticipated that this application will be able to reduce the excessive use of paper and minimize office operational costs. Furthermore, it is anticipated that this technology will enable employees to examine real-time leave data.